Standards for the development and methodology of the 2023 IWGDF guidelines - Sicco A. Bus; Matilde Monteiro‐Soares; Frances L. Game; Jaap J. van Netten; Jan Apelqvist; Robert Fitridge; Éric Senneville; Nicolaas C. Schaper (2023)
Abstract Aims Diabetes‐related foot disease is a major source of patient burden and societal costs. Investing in evidence‐based international guidelines on diabetes‐related foot disease is important to reduce this burden and costs, provided the guidelines are focused on outcomes important to key stakeholders and are evidence‐based and properly implemented. Materials and Methods The International Working Group on the Diabetic Foot (IWGDF) has published and updated international guidelines since 1999. The 2023 updates were made using the Grading of Recommendations Assessment Development and Evaluation evidence‐to‐decision framework. This concerns formulating relevant clinical questions and important outcomes, conducting systematic reviews of the literature and meta‐analyses where appropriate, completing summary of judgement tables, and writing recommendations that are specific, unambiguous and actionable, along with their transparent rationale. Results We herein describe the development of the 2023 IWGDF Guidelines on the prevention and management of diabetes‐related foot disease, which consists of seven chapters, each prepared by a separate working group of international experts. These chapters provide guidelines related to diabetes‐related foot disease on prevention; classification of diabetes‐related foot ulcer, offloading, peripheral artery disease, infection, wound healing interventions, and active Charcot neuro‐osteoarthropathy. Based on these seven guidelines, the IWGDF Editorial Board also produced a set of practical guidelines. Each guideline underwent extensive review by the members of the IWGDF Editorial Board as well as independent international experts in each field. Conclusions We believe that the adoption and implementation of the 2023 IWGDF guidelines by healthcare providers, public health agencies, and policymakers will improve the prevention and management of diabetes‐related foot disease, and subsequently reduce the worldwide patient and societal burden caused by this disease.